The Moral Duty to Struggle for Gender Equality for Women - Mark Omorovie Ikeke (Editura Universităţii Aurel Vlaicu Arad, 2021)
Despite the many international human rights declarations affirming the equality of men and women, and the techno-scientific accomplishments of humanity, in many non-Western societies and indigenous cultures there are still much discrimination against women. The discrimination and violence against women on the basis of their sex and their being perceived as subservient to men by some cultures, societies and persons are morally unacceptable. Discrimination and violence against women are wrong for they offend against the ontological status of women as human beings; violate their human dignity/ rights as persons. The arguments that some persons have used to treat women as unequal to men are flawed. It is an issue of morality for it speaks of how human beings should act. This paper uses a critical analytic, hermeneutics and evaluative methods to examine the issues. The issues of gender equality will be dissected and interrogated. The value in gender equality through all these methods will be highlighted. The paper finds that there are gender inequalities still prevalent in some parts of the world. The paper concludes that all societies, cultures and persons have a moral duty to struggle against gender inequalities. This will help to create a more harmonious world.